Synthesis, Spectral and Antibacterial Studies of 4-Aminoantipyrine Based Tetradentate Ligand and Its Cu(II), Ni(II) and Co(II) Metal Complexes - Kumar, Ashish; Khasa, Ashwani; Sharma, R.G.; Rai, Amit (Asian Journal of Chemistry, 2011)
Four Schiff base metal complexes of Cu(II), Ni(II), Co(II) have been synthesized from a new tetradentate ligand, 2-((E)-1,5-dimethyl-2-phenyl-3-((E)-quinolin-8-methyl)-2,3-dihydro-1Hpyrazol- 4-ylimino)methyl)phenol. The ligand and its metal complexes have been charac-terized on the basis of elemental analysis, electronic, infrared, 1H NMR and 13C NMR spectral studies. On the basis of electronic spectral studies, for Cu(II) complex, deformed tetrahedral, Co(II) complex, tetrahedral and Ni(II) complex octahedral geometry has been proposed. The in vitro antimicrobial activity of the investigated compounds was tested against the bacteria such as Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and fungi-Candida albicans and Rhizopus stolonifer. The data indicate that most of the metal complexes have higher antimicrobial activity than the free ligand.